Solution Blow Spinning Poly(vinyl alcohol) Sub-microfibers Produced from Different Solvents - Jessica Lima Viana; Thiago França; Cicero Cena (Orbital: The Electronic Journal of Chemistry, 2020)
Poly (vinyl alcohol) (PVA) presents a good chemical stability at room temperature, and interesting physical and mechanical properties that enable a wide range of applications of this material. The relationship between the type of polymer-solvent interaction and the physical properties of the gel can be considered, as a key factor to produce PVA micro- and nanofibers by solution blow spinning (SBS) technique. In this work, the influence of changes in the polymer-solvent interaction as a function of the solvent composition on SBS fiber formation are presented. The low molecular weight PVA solutions were obtained by dissolving the PVA in deionized water, and then adding a more volatile solvent to adjust the final concentration at 0.08 g/mL. The addition of different solvents was performed to modify the chemical nature of the solvent and consequently the polymer-solvent interaction. The viscosity measurements were performed as a function of temperature and shear rate. The rheological characterization of the solutions revealed significant changes in the viscosity value as a function of the solvent nature, although the solution´s rheological behavior showed no significative changes. Finally, the solutions showed potential to produce homogeneous PVA sub-microfibers by solution blow spinning technique.DOI: http://dx.doi.org/10.17807/orbital.v12i1.1169